Danian (Early Paleocene) echinoids from the Roca Formation, northern Patagonia, Argentina - Martínez, Sergio; del Río, Claudia Julia; Concheyro, Graciela (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen)
Stratigraphically well-constrained echinoids from the Roca Formation in the province of Rio Negro (Patagonia, Argentina) are analysed in detail. The poorly known Linthia? joannisboehmi OPPENHEIM in BÖHM, 1903, recently reassigned to Paraster, is demonstrated to comprise in fact two distinct species, Linthia? joannisboehmi and Linthia parmae n. sp. In addition, specifically indeterminate species of Plesiaster and Hemiaster and a basal holasteroid are recorded. The analyses of calcareous nannofossil assemblages of the echinoid-bearing strata document their early Paleocene (Danian) age, which has an impact on patterns of survivorship across the K/Pg boundary. Fil: Martínez, Sergio. Universidad de la República. Facultad de Ciencias; Uruguay Fil: del Río, Claudia Julia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Concheyro, Graciela. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina